DECOLORIZATION KINETICS FROM COFFEE EFFLUENT WITH PHOTO-FENTON REACTION - Lieke Riadia (Purifikasi, 2011)
Coffee effluent contains a high amount of dark brown pigments. When this waste is released in the river, itwill block the sun ray and disturb the photosynthesis process. The decolorization of coffee effluent usingphoto-Fenton and Fenton processes is presented in this paper. On the photo-Fenton reaction, UV light, ionFe(II) and H2O2 will produce •OH. This will react with organic contaminant, so the color of the effluent willbe changed from brown to yellow, and finally became a clear solution. On the Fenton process, reactionoccurred without the existence of UV light. The rate of this decolorization is slower than photo-Fentonreaction. The reaction consists of three phases, the first phase happen when H2O2 is added to the reactor andthe color changes rapidly, the color of the solution start to be removed fast (second phase) and then it becamefaster and there were no more changes in its color (third phase). The color removal rate for second phase atthe coffee effluent concentration of 250 ppm,300 ppm, 400 ppm were : r = -0,0322 (Abs)² ; r = -0,0271(Abs)²; r = -0,0196 (Abs)², whereas the color removal rate for third phase at the coffee effluent concentrationof 250 ppm, 300 ppm, 400 ppm were : r = -0,0049 (Abs) ; r = -0,0211 (Abs) ; r = -0,005 (Abs)